A new species of planthopper in the genus Haplaxius (Hemiptera: Auchenorrhyncha: Fulgoroidea: Cixiidae) from coconut palm (Cocos nucifera) in Costa Rica - Barrantes, Edwin A. Barrantes; Echavarria, Marco A. Zumbado; Bartlett, Charles R.; Helmick, Ericka E.; Bahder, Brian W. (Zootaxa, 2021)
Haplaxius is a large genus of cixiid planthoppers that is widespread in the New World and economically important due to the role of H. crudus in transmitting palm lethal decline phytoplasmas. A new species of Haplaxius, here described as Haplaxius pocococo sp. n., was discovered during survey work on palms in north-central Costa Rica. Placement in Haplaxius is supported by sequence analysis of the COI and 18S genes relative to congeners and by morphological characters.